About Commons And Tragedıes Revıewıng a Concept - Coelho, Manuel; Filipe, José António; Ferreira, Manuel Alberto M. (Acta Scientiae et Intellectus, 2024)
Metaphors are very important for Economics as Science, both in terms of reasoning and rationale, and in its teaching. The "Tragedy of the Commons" is a very particular example, originating in the scientific area of the Natural Resources and Environment Economy of one of these metaphors and their effects. Dealing with property rights lends itself to misunderstandings since important researchers in this area do not distinguish between "common property" and "nonproperty", although this definition is crucial for the design of the Natural Resources Management Policy. Along this paper, it is intended to rectify this confusion and to establish an adequate conceptualization.